Antibacterial Activity Test of Mahkota Dewa Fruit (Phaleria macrocarpa) Extract against Escherichia Coli Bacteria - Dwi Norma Retnaningrum; Wenny Rahmawati (EMBRIO: Jurnal Kebidanan, 2023)
Exposure to Escherichia coli during pregnancy may cause serious problems such as anemia, premature birth and an increased risk of inflammation of the lining of the brain in the fetus. Mahkota Dewa (Phaleria macrocarpa) is a medicinal plant that is widely known and used to treat allergies and chronic diseases. One of the compounds contained in Mahkota Dewa is flavonoids. There is certain mechanism of action of flavonoids in inhibiting bacteria namely by damaging the cytoplasmic cell wall in bacteria. This study aims to analyze the antibacterial properties of various flavonoid concentrations of Mahkota Dewa fruit (Phaleria macrocarpa) extract against Escherichia coli bacteria through a laboratory experimental study design by testing the antimicrobial potency of the well method, namely 10percent, 20percent, 40percent, 60percent, 80percent and 100percent. Statistical analysis using One-Way Anova Test showed a significant difference between changes in the concentration of flavonoids in Mahkota Dewa fruit extract and the inhibition zones towards the growth of Escherichia coli bacteria (p less than 0.05). Pearson correlation test showed a very strong relationship with a positive direction (r equals 0.874) which indicated that the higher the concentration of flavonoids in Mahkota dewa fruit extract, the stronger the antimicrobial effect. Based on the study findings, it can be concluded that the flavonoid extract in Mahkota Dewa fruit extract had an antimicrobial potential against Escherichia Coli in vitro.